A new species of Echeveria ser. Nudae (Crassulaceae) from Jalisco, Mexico, and a new combination - Jimeno-Sevilla, H. David; Hernández-Campos, J. Daniel; Rosales-Martínez, C. Santiago; Posadas-Trejo, Karla Gabriela (Phytotaxa, 2025)
A new species, Echeveria machucae (ser. Nudae, Crassulaceae), is described from specimens collected in El Jacal, Atenguillo municipality, Jalisco. It is a putative close relative of E. flammigera, from which it differs by having larger stems, larger leaves, racemose to occasionally thyrsiform inflorescences, longer pedicels, presence of yellow corollas, and wider yellow nectary scales. It is also compared with E. multicaulis, E. pringlei, and E. longisepala, the latter raised here at the species level based on morphological evidence. A distribution map with records of the aforementioned species is presented.